The influence of work culture on employee performance at KOMIDA Cariu branch office, Bogor Regency - Yanto Lesmana; Yudi Kristanto; Aliy Rasyid; Dani Sumantri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the influence of work culture on the performance of KOMIDA employees of the Cariu branch office of Bogor Regency. The sub-variables studied from work culture are habits, regulations, and values. While employee performance is the quantity, quality, time utilization, attendance rate and common goals. The research method used for this study is quantitative, with a significance level of α = 0.05 (5%) and a confidence level of 95%. While the sample used was 35 respondents where all populations were sampled and used population samples, data collection methods by distributing questionnaires to employees of KOMIDA Bogor Regency Cariu Office. Based on the calculation results, a correlation coefficient of r = 0.711 is obtained which means a high level of relationship and a determination coefficient of R = r2 = 0.506 shows that 50.6% diversity in Performance can be understood by diversity in Work Culture. Testing the significance of the correlation obtained tcount (5.808 > t table (1.671) at = 0.05, then Ho rejected Ha accepted. And it can be concluded that there is an influence between work culture on the performance of employees of KOMIDAKantor Cariu branch, Bogor Regency.